Experimental study on the buckling of composite cylinders with reinforced circular hole under hydrostatic pressure - Zhun Li; Xinhu Zhang; Kechun Shen; Jing Liu; Jian Zhang; Guang Pan (Defence Technology)
In this paper, a type of reinforcing structure for composite shell with single and through hole is presented. The experimental tests for the composite shells without hole, with single hole and reinforced structure, with through hole and reinforced structure subjected to hydrostatic pressure were carried out by the designed experimental test system. The mechanical responses of the composite shells under hydrostatic pressure are obtained by the high-speed camera and strain measurement. The results show that the entire deformation process of the shell can be divided into three: uniform compression, ''buckling mode formation'' and buckling. The ''buckling mode formation'' process is captured and reported for the first time. For the composite shell with single hole, the proposed reinforcing structure has a significant reinforcement effect on the shell and the buckling capacity of the shell is not weaker than the complete composite shell. For the composite shell with through hole, sealing effect can be achieved by the proposed reinforcing structure, but the buckling capacity of the shell after reinforcement can only reach 77% of the original buckling capacity.